AN ATTEMPT AT THE COMPARATIVE ANALYSIS OF FOREIGN AND RUSSIAN STYLE OF ADVERTIZING TRAVEL SERVICES - KURBATSKAYA, Tatyana Borisovna; DOBROTVORSKAYA, Svetlana Georgievna; USTYN, Pavel Nikolayevich (Journal of Environmental Management and Tourism, 2016)
In this paper, the specifics of advertizing travel services are analyzed, as it is represented in different countries. The authors refer to advertisements offered by the most recognized travel agencies of Europe (Portugal, Italy and the United Kingdom), Asia (represented by Thailand), North (the USA and Canada) and South America (Brazil), and of Russia, as well. We have defined the specifics of advertizing, aimed at European, Asian, American and Russian consumers. Some problematic points have been detected in the advertizing messages, designed by Russian travel agencies. We give the analysis of the advertizing messages employed in the Russian advertizing of travel services, using particular examples, created by a travel agency and placed in the social network “Vkontakte”.
Keywords: Advertizing; symbols; psychological influence; images